High‐strength, electrically insulated industrial meta‐aramid paper reinforced with polyethylene terephthalate microfibre pulp in a sandwich structure - Meijun Chen; Songjun Yao; Guobin Zhu; Mengyun Wu; Zhiying Li; Siwei Xiong; Shiwen Yang; Hua Wang; Liangbo Zhu; Luoxin Wang (High Voltage)
Abstract The weak interfacial strength and porous structure of the meso‐aramid paper cause mechanical and insulating deficiencies. Enhancing density, regulating pore structure, and improving interfacial interactions of meso‐aramid are crucial for promoting the performance of meso‐aramid papers. A PMIA/polyethylene terephthalate (PET) composite paper was prepared using the wet method with meso‐aramid short cut fibres (PMIA) and PET pulp as raw materials. The sandwich‐structured PMIA/PET paper was achieved by covering PET microfiber non‐wovens served as the surface layer while the PMIA/PET composite paper acted as the core layer. During the high‐temperature hot pressing process, the PET pulp transformed into a viscous melt that coated on aramid fibres in between layers, forming a typical ‘reinforced concrete’ interface structure within the core layer of the PMIA/PET composite paper. The PET non‐wovens on top and bottom surfaces were converted into a dense PET film that filled and covered the holes and defects in the PMIA/PET composite paper. This unique structure enabled the sandwich‐structured PMIA/PET composite paper to exhibit excellent tensile strength (80.41 N/cm) and breakdown strength (56.35 kV/mm), surpassing most reported performances of meso‐aramid papers in literature. This work not only provides novel insights for preparing high‐performance meso‐aramid papers, but also shows potential applications for other materials and structures.